De-escalation of anti-CD20 monoclonal antibodies to low-moderate efficacy disease-modifying treatments (DMTs) in patients with relapse-remitting multiple sclerosis: the initial Iranian experience - Sepideh Paybast; Nasim Rezaeimanesh; Abdorreza Naser Moghadasi (Babol University of Medical Sciences, 2025)
Background: Anti-CD20 are among the high-efficacy DMTs commonly used in treating multiple sclerosis (MS). Long-term safety data on anti-CD20s are limited. There is convincing evidence of hypogammaglobulinemia in the long-term use of anti-CD20s, raising the likelihood of infection. Accordingly, there is an unmet need for de-escalation therapy in stable patients to reduce adverse events. Herein we aimed to describe our experience with ten relapse-remitting MS (RRMS) patients who were switched from anti-CD20s to the low-moderate efficacy DMTs. Methods: This cohort study was conducted between January 2020 and February 2023 at the MS Research Center of Sina Hospital, Tehran, Iran, to identify the characteristics of RRMS patients who were switched from anti-CD20s to low-moderate efficacy DMTs within 12 months of the last anti-CD20 infusion. Patients were then followed up to 18 months after de-escalation. Results: All patients were females, with a mean age of 39.3±2.53-year-old and a mean disease duration of 9.7±1.39 years. After a mean of 2.95±0.44 years of treatment with anti-CD20s, patients were de-escalated to INF-β1a (n=5), dimethyl fumarate (DMF) (n=3), fingolimod (n=1), and teriflunomide (n=1). The main reason for anti-CD20 discontinuation was an infectious concern. Within 18 months of follow-up, no patient developed clinical or MRI activity. Additionally, we did not find evidence of disability progression in any patients (P=0.13). Conclusion: The present study is a real-world experience of de-escalating anti-CD20s to low-moderate efficacy DMTs, which suggests that at short-term follow-up, de-escalating anti-CD20s appeared to be effective and safe in RRMS patients.